Diagnosis of precocious puberty due to tuber cinereum hamartoma by clinicoradiologic correlation - Chopra, Rahul; Arora, Priya; Yadav, Rohtas K. (International Journal of Contemporary Pediatrics, 2017)
We present a case of a 3 year male child who presented with precocious puberty. Endocrinological studies revealed increased LH and increased testosterone. Bone age was 8 years. MR Imaging showed hypothalamic mass isointense to brain parenchyma on T1-WI and hyperintense on T2-WI, without contrast enhancement. Typical clinical presentation, endocrinological studies and MRI features strongly favoured the diagnosis of tuber cinereum hamartoma. This case is presented to emphasize the importance of clinicoradiologic correlation in the diagnosis of precocious puberty due to tuber cinereum hamartoma.